PEMASARAN SYARIAH BERBANTUAN MEDIA SOSIAL: KONTESTASI STRATEGIS PENINGKATAN DAYA JUAL (An-Nisbah: Jurnal Ekonomi Syariah, 2019)
The emergence of instant products has a major impact on people's perspectives and behavior. Many people do not want to be difficult in owning a house, so PT Karya Cipta Sakinah uses this great opportunity to build a medium-sized business that is engaged in the developer. The business that was carried out began with the use of own capital which is now expanding into a larger business aimed at supporting the government's "Million Houses" program. The sharia marketing strategy implemented by PT Karya Cipta Sakinah which prioritizes sharia elements brings a lot of blessings, this has a big impact on the increase in consumer response and blessed profit. PT Karya Cipta Sakinah initially used promotional strategies through print media which were considered less effective. And now increasingly expanding its wings by using a Facebook account as an accurate means of proper promotion to facilitate the delivery of business product information to the wider community. In this case the researcher uses the research method "Qualitative Descriptive Analysis" with data collection techniques "observation, interviews and documentation"